2014
DOI: 10.1111/ijcp.12540
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and tolerability of tarafenacin, a new muscarinic acetylcholine receptor M3 antagonist in patients with overactive bladder; randomised, double-blind, placebo-controlled phase 2 study

Abstract: Tarafenacin 0.4 mg decreased the number of micturitions in patients with OAB after 12 weeks compared with placebo, and the dose-response relationship of tarafenacin 0.2 and 0.4 mg was confirmed. Both dose levels of tarafenacin were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…). The full texts of 119 trials were reviewed, and 38 were ultimately included in the analysis . Of the 39 potentially relevant trials additionally identified from http://ClinicalTrials.gov, three were included in the analysis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). The full texts of 119 trials were reviewed, and 38 were ultimately included in the analysis . Of the 39 potentially relevant trials additionally identified from http://ClinicalTrials.gov, three were included in the analysis .…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved a total of 41 trials involving 22 328 patients (14 292 randomized to a treatment group and 8036 to a placebo group) that met the selection criteria. The number of participants used in analyses of the mean number of micturitions in 24 h, mean number of incontinence episodes in 24 h, mean number of urgency episodes in 24 h, mean volume voided/micturition,, mean number of urgency incontinence episodes in 24 h,, and mean number of nocturia episodes were 22 311, 8738, 14 178, 18 763, 10 072, and 9072 patients, respectively. The main characteristics of the 41 trials are described in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The initial results seem to indicate that the action of the drug begins quickly, reaching maximum blood concentration within 4h after swallowing, and T 1/2 -within 35 h, as a result of which it can be taken once a day. No significant cardiovascular adverse events have been noted so far [2].…”
Section: New Antimuscarinicsmentioning
confidence: 87%
“…A representative candidate antimuscarinic agent, tarafenacin, is known to have superior selectivity to M3 in comparison with M2; it was shown to have 200 times greater selectivity [18] and its characteristics include less constipation than conventional anticholinergic agents and dry mouth as the most common side effect [19]. THVD-201 (Tolenix) and THVD-202 have been developed for a once daily or twice daily regimen, which is combination of tolterodine, an antimuscarinics, and pilocarpine, a modified-release muscarinic agonist [20].…”
Section: Next Generation Drugs For Oabmentioning
confidence: 99%